A concise guide to fluorescent cell cycle reporters for live-cell imaging - Wang, Jinyu; Li, Yige; Luo, Jia; Sharvia, Septavera; Chan, Kuan Yoow (Frontiers in Cell and Developmental Biology, 2025)
The cell cycle is a fundamental process vital for organismal growth and stability. Its dysregulation underlies many human diseases, in particular cancers, making its monitoring essential in biological research. Genetically encoded fluorescent cell cycle reporters have become indispensable tools for studying the cell cycle, providing invaluable insights into cell cycle dynamics at single-cell resolution. A variety of fluorescent reporters, including FUCCI, kinase translocation reporters, and DNA replication foci-based systems, have been developed to track cell cycle progression. Each reporter measures distinct cell cycle specific processes to determine the cell cycle status, exhibiting distinctive strengths and limitations. In this review, we provide an overview on the commonly used cell cycle reporter systems. We then highlight the strengths and weaknesses of the various cell cycle reporter systems to guide researchers in selecting the most appropriate reporters for their specific needs. Finally, we discuss recent approaches where various cell cycle reporters are combined to overcome the limitations of each system. Collectively, single cell analysis with these reporters are transforming the study of cell cycle regulation, advancing our ability to interrogate a fundamental process that governs cell fate and function.